Effectiveness Of Giving Cinnamon Brewing (Cinnammon Burmanni) On Blood Glucose Levels In Elderly People With Type 2 Diabetes Mellitus At Hospital X (Comprehensive Health Care, 2024)
Background: Health problems of diabetes mellitus can affect organs of the body and as a result can cause various kinds of complaints of disease. People often pay less attention to lifestyle, such as daily food consumed. Objective: The purpose of this nursing care is expected to be able to understand, explain and apply evidence-based practices in professional nursing, after the Administration of Cinnamon Burmanni Tea on Blood Glucose Levels in the Elderly with Type 2 Diabetes Mellitus at Hospital X. Research Method: The evidence-based nurse (EBN) design used is Quasy Experiment, especially pretest-posttest design. Namely by conducting observations before and after the control group intervention. There are two intervention groups, namely 2 groups that are given Cinnamon Burmanni Tea on Blood Glucose Levels in the Elderly for 4 consecutive days and carried out 2 times a day. Results: The results of the control group showed an average blood glucose level with a mean value of 2.00 mg / dl (SD = 0.000). Meanwhile, in the intervention group, blood glucose levels in elderly DM patients after giving cinnamon infusion (Cinnammon Burmanni) with a mean value or average blood sugar level of 1.25 (SD = 0.500) with a p-value (0.024) or less than the significance value of p-value <0.05. Conclusion: There is an effect of giving cinnamon infusion (Cinnammon Burmanni) on reducing blood glucose levels in elderly patients after intervention Keywords: Cinnamon Infusion (Cinnammon Burmanni), GDS, Type 2 Diabetes Mellitus, Elderly